PENGARUH PERMAINAN BONEKA TANGAN TERHADAP KECEMASAN ANAK USIA PRASEKOLAH AKIBAT HOSPITALISASI DI RSUD LABUANG BAJI MAKASSAR - Sunarti Sunarti (FORIKES, 2021)
Preschoolers are very susceptible to disease so they must undergo hospitalization. Hospitalization can have an impact in the form of anxiety so that children are not cooperative in accepting nursing actions and aggravating health conditions. One of the therapies used to reduce anxiety in children is by playing with hand puppets. The purpose of this study was to determine the effect of hand puppet play on the anxiety of preschoolers due to hospitalization in Labuang Baji Regional Hospital Makassar. The research method uses analytic survey method with a Pre-Experimental approach namely One Group Pre-test and Post-test. The population in this study were all pediatric patients aged 3-6 years in the Minasa Wedge Room Labuang Baji Hospital Makassar City with sampling techniques, namely a total sampling of 20 samples using the Paired Sample T Test with a significant level of α = 0.005. The results showed that child anxiety before being given hand puppet play therapy with severe anxiety as much as 6 (30%) and moderate anxiety as much as 14 (70.0%), after being given hand puppet play therapy, western anxiety was absent, moderate anxiety was 12 (60 %) and mild anxiety of 8 (40.0%). Statistical test results show there is an influence of hand puppet play on pre-school age children's anxiety due to hospitalization with the value ρ-Value = 0,000 (ρ